Automation of Library Resources Utilization (Journal of Pharmaceutical Negative Results, 2022)
The library is one of the University's front-line services. Managing a large number of students and faculty is difficult, especially when it comes to tracking their attendance each time they visit the library. The librarian's goal is to provide excellent service to its clients. Thus, the Automation of Library Resources Utilization at the San Mateo Campus was created using the Agile Development Process, which included several stages: Design, Build, Configure, Test, and Release. Descriptive statistics, particularly mean, were also used to analyze the data in terms of student feedback and the validity of the developed application as judged by the clients. During this process, problems in the manual operation were identified and addressed by the automation. As a result, in terms of functional adequacy, system quality, adaptability, usefulness, stability, safety, maintainability, and portability, Automation of Library Utilization has been designed and is in compliance with ISO 25010. Furthermore, respondents identified challenges to the automation of library utilization as part of the development process that follows a continuous improvement of system life cycle to maintain being a Positive Aspect when it comes to ISO 9001:2015.